Influence of epidermal growth factor (EGF) and hydrocortisone on the co‐culture of mature adipocytes and endothelial cells for vascularized adipose tissue engineering. (4th March 2016) - Huber, Birgit; Czaja, Alina Maria; Kluger, Petra Juliane
Abstract: The composition of vascularized adipose tissue is still an ongoing challenge as no culture medium is available to supply adipocytes and endothelial cells appropriately. Endothelial cell medium is typically supplemented with epidermal growth factor (EGF) as well as hydrocortisone (HC). The effect of EGF on adipocytes is discussed controversially. Some studies say it inhibits adipocyte differentiation while others reported of improved adipocyte lipogenesis. HC is known to have lipolytic activities, which might result in mature adipocyte dedifferentiation. In this study, we evaluated the influence of EGF and HC on the co‐culture of endothelial cells and mature adipocytes regarding their cell morphology and functionality. We showed in mono‐culture that high levels of HC promoted dedifferentiation and proliferation of mature adipocytes, whereas EGF seemed to have no negative influence. Endothelial cells kept their typical cobblestone morphology and showed a proliferation rate comparable to the control independent of EGF and HC concentration. In co‐culture, HC promoted dedifferentiation of mature adipocytes, which was shown by a higher glycerol release. EGF had no negative impact on adipocyte morphology. No negative impact on endothelial cell morphology and functionality could be seen with reduced EGF and HC supplementation in co‐culture with mature adipocytes. Taken together, our results demonstrate that reduced levels of HC are needed for co‐culturing mature adipocytes and endothelial cells. In co‐culture, EGF had no influence on mature adipocytes. Therefore, for the composition of vascularized adipose tissue constructs, the media with low levels of HC and high or low levels of EGF can be used.